Simulated Future Climates for Ethiopia Using MIT-IGSM HFDs Based on CMIP5 - International Food Policy Research Institute; Massachusetts Institute of Technology (International Food Policy Research Institute, 2024)
The dataset consists of high-resolution climate projections spanning 50 years, capturing spatial and temporal variations in temperature, precipitation, and extreme weather events. These climate inputs were combined with agricultural models to simulate the frequency, intensity, and impact of weather events on the yields of key crops, such as maize, in Ethiopia. It integrates hybrid frequency distributions (HFDs) from the Massachusetts Institute of Technology Integrated Global Systems Model (MIT-IGSM) with detrended gridded historical climates from Princeton Global Forcings. Using a Gaussian quadrature routine, 455 representative climate scenarios were selected for Ethiopia under each emissions scenario (SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5). This comprehensive dataset provides critical insights into the risks posed by climate change to food security and serves as a valuable resource for researchers and policymakers aiming to develop adaptive strategies for sustainable agriculture.